IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF BERBASIS SATUA PAN MERI DALAM MENANAMKAN KARAKTER KEJUJURAN SISWA SEKOLAH DASAR - Ida Bagus Yoga Swadnyana; I Wayan Sujana; Ni Putu Devi Wedayanti; Melly Cahyani, Putu; Ni Luh Putu Wirasanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the importance of instilling honesty character in elementary school students, which is still influenced by external factors such as fear of reprimands and punishment. This study aimed to describe the implementation of a cooperative learning model based on Satua Pan Meri in instilling honesty character among students at SD Negeri 5 Ketewel. The study used a qualitative approach with a descriptive research design. The research subjects consisted of third-grade students and the classroom teacher. Data were collected through observation, interviews, and documentation. The data were analyzed descriptively through data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the cooperative learning model based on Satua Pan Meri increased students’ involvement in the learning process and supported the development of honesty character. Changes in students’ behavior were reflected in their courage to admit mistakes, complete assignments independently without cheating, speak honestly, and become more responsible for assigned tasks. The use of Satua Pan Meri as a local wisdom-based learning medium helped students understand the value of honesty more easily because the stories were closely related to their daily lives and culture. The cooperative learning model based on Satua Pan Meri can be used as an alternative learning approach to instill honesty character in elementary school students.